Intensification of Very Wet Monsoon Seasons in India Under Global Warming - Anja Katzenberger; Anders Levermann; Jacob Schewe; Julia Pongratz (Geophysical Research Letters)
Abstract Rainfall‐intense summer monsoon seasons on the Indian subcontinent that are exceeding long‐term averages cause widespread floods and landslides. Here we show that the latest generation of coupled climate models robustly project an intensification of very rainfall‐intense seasons (June–September). Under the shared socioeconomic pathway SSP5‐8.5, very wet monsoon seasons as observed in only 5 years in the period 1965–2015 are projected to occur 8 times more often in 2050–2100 in the multi‐model average. Under SSP2‐4.5, these seasons become only a factor of 6 times more frequent, showing that even modest efforts to mitigate climate change can have a strong impact on the frequency of very strong rainfall seasons. Besides, we find that the increasing risk of extreme seasonal rainfall is accompanied by a shift from days with light rainfall to days with moderate or heavy rainfall. Additionally, the number of wet days is projected to increase.